Rancang Bangun Bahan Ajar Digital Berbasis Ekopedagogik Approach - Dede Margo Irianto; Yusuf Tri Herlambang; Hana Yunansah; Rahman Wahid (NATURALISTIC : Jurnal Kajian Penelitian Pendidikan dan Pembelajaran, 2022)
This Study aims to describe the Design of Teaching Materials Based Digital Ekopedagogik Approach. The research method used is the method of Design and Development using model 4-D. Data collection techniques used were questionnaires. The research results found showed that the medium of digital teaching materials that has been developed is feasible to use based on the assessment of the experts to obtain the percentage of 97.5% in terms of material, for 82.5% in terms of the media, and 100% in terms of language. Summary assessment of teaching materials by students gain percentage 96,87% in terms of the content of the material, 100% in terms of use, and 100% in terms of appearance.